Factors associated with depressive symptoms in pharmacy residents. (15th December 2018) - Williams, Evan; Martin, Sarah L.; Fabrikant, Alla
Abstract : Purpose: Results of a study to determine factors that contribute to depressive symptoms among pharmacy residents are reported. Methods: In a time series study conducted during the 2015–16 residency year, pharmacy residents nationwide were invited to participate in a series of online surveys administered at 3 time points. Information specific to the residency program and external factors was compared with residents' scores on the 9-item Patient Health Questionnaire. Factors associated with depressive symptoms were determined using logistic regression controlling for history of depression and current use of medication for depression. Results: The survey response rate in March 2016 was 21.2%. The strongest predictor of depressive symptoms was perceived stress level (odds ratio [OR], 2.45), while getting enough sleep was the strongest protective factor (OR, 0.39). In multivariate analysis, stress level (OR, 1.84) and not having family nearby (OR, 1.45) were significantly associated with depressive symptoms. Conclusion: High levels of stress, living with family or not having family within driving distance, a high number of hours worked, and a high number of days between having a full 24 hours off duty were associated with higher levels of depressive symptoms, while high levels of family support, an outpatient and/or clinic residency setting, supportive directors and preceptors, effective teaching methods, well-structured and organized programs, clear expectations of residents, having enough days off, and adequate sleep were associated with decreased reporting of depressive symptoms among pharmacy residents in a national study.